Uji Daya Racun Terusi Untuk Mencegah Serangan Rayap Kayu Kering Pada Kayu PARA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Dry wood termite makes a considerable damage to wood in construction, while high grade and durable wood becomes more and more expensive and less available. Preserving perishable wood having moderate mechanical properties such as para (Hevea brassiliensis Muell. Arg.) wood against dry wood termite using a cheap wood preservative is very desirable. Research on temsi (CuSO4.5H20) toxicity against dry wood termite (Cryptotermes cynocephalus Light) was conducted on para wood sample blocks to see the smallest and the shortest, terusi concentration and cold soaking duration, which was effectively inhibit or avoid the (termite) attack Concentrations used were 1, 3 and 5% tenisi solution in water. Para wood sample blocks were 5 by 5 by 5 cm. Treatment was cold soaking the wood block in terusi solution for 1, 2, 3 and 4 days. Using 5 replications, the research was set in a Completely Randomized Design. After the blocks had been treated and air dried, a small glass cylinder of 3 cm diameter was glued uprightly on the width surface of each block and 50 termites were introduced into each cylinder for 60 days. Terusi retention, termite mortality and weight difference of the blocks after 60 days were measured. The results showed that terusi was effective to inhibit the termite attack on para wood and the smallest and the shortest effective, terusi concentration and cold soaking duration was 3% and two days.